KAJIAN BIAYA OPERASIONAL KENDARAAN UMUM JALUR TERMNAL MARDIKA-AIR SALOBAR DI KOTA AMBON - Walsen, Selviana (Jurnal Teknik Sipil, 2014)
Operational cost of transportation route by Air Salobar on Ambon City is a cost incurred by public transport entrepreneurs in running the business operation, while achieving the goal of safe transportation desires, comfortable, economical and smooth , need to pay attention to the condition of the existing public transportation that operates at the route. Especially services that are considered very meggangu the city transport service users as well as in Indonesia today , and in particular Ambon city transport routes Mardika’s Terminal – Air Salobar. So it’s it is precisely when reviewing how service levels to be very low right now. So that needs to be revisited once the city transport fares set by the government and compared to public transportation operating costs to be incurred by the manager of public transportation to take a step back calculation. Public transportation cost calculations are calculated based on the calculation of fixed and variable costs. For variable costs consisting of fuel costs, the cost of lubricating oil, tire usage costs , driver wages and repair costs. Vehicle operating costs per passenger per trip Mardika’s Terminal – Air Salobar IDR 2000 of the calculation results, obtained vehicle operating costs per passenger per trip is greater than revenue means businesses operate vehicles transport on this route loss.